A Longitudinal Examination of Alcohol-Related Blackouts as a Predictor of Changes in Learning, Memory, and Executive Function in Adolescents - Lorkiewicz, Sara A.; Baker, Fiona C.; Müller-Oehring, Eva M.; Haas, Amie; Wickham, Robert; Sassoon, Stephanie A.; Clark, Duncan B.; Nooner, Kate B.; Tapert, Susan F.; Brown, Sandra A.; Schulte, Tilman (Frontiers in Psychiatry, 2022)
Introduction: In adolescents, the relationship between alcohol-related blackouts (ARBs) and distinct cognitive changes lasting beyond intoxication is unclear. We examined ARBs as a predictor of persistent changes in the development of learning, memory, and executive function in participants from the National Consortium on Alcohol and Neurodevelopment in Adolescence (NCANDA) study. Methods: Descriptive analyses of the NCANDA sample (N = 831, 50.9% female, 12-21 years at baseline) identified ARB patterns within participants with an ARB history (n = 106). Latent growth curve modeling evaluated ARB-related performance changes on four neuropsychological measures across five years, excluding baseline data to reduce the magnitude of practice effects over time; Sullivan et al., 2017 (n = 790). Measures included the Penn Conditional Exclusion Test (PCET), Penn Letter N-Back Test (PLBT), Penn Facial Memory Test immediate (PFMTi) and delayed (PFMTd) recognition trials, and the Rey Complex Figure Test copy (RCFTc), immediate recall (RCFTi), and delayed recall (RCFTd) trials. Multivariate models were fit for raw accuracy scores from each measure, with ARB history (i.e., presence of past-year ARBs) as the main independent variable. Age, sex, race, socioeconomic status, assessment site, and alcohol use (i.e., past-year frequency) were included as covariates. Interaction effects between ARB history and alcohol use frequency were tested. Results: By year five, 16% of participants had experienced at least one ARB (59% of whom reported > 1 ARB and 57% of whom had an ARB lasting > 1 hour). After controlling for demographics and alcohol use, ARB history predicted attenuated PFMTd performance growth at year one. Interaction effects between ARB history and alcohol use frequency predicted attenuated PFMTd performance growth at years one and two. ARB history predicted attenuated RCFTi and RCFTd performance growth by year four, but not PCET or PLBT performance over time. By contrast, greater past-year alcohol use predicted attenuated PFMTi and PFMTd performance growth between years two and four in adolescents without an ARB history. Conclusions: We found that ARBs predict distinct, lasting changes in facial episodic memory and visual incidental learning and memory, with results suggesting that the developing brain is vulnerable to ARBs during adolescence and emerging adulthood.